ANALISIS KONFLIK KONI DAN KOI TERKAIT TUGAS DAN FUNGSI BERDASARKAN UU NO. 3 TAHUN 2005 MENGENAI SISTEM KEOLAHRAGAAN NASIONAL - Boy Anugerah; Amar Ahmad (POLITEKNIK LP3I JAKARTA, 2017)
This study described about conflict between KONI and KOI related to task and function according to UU No. 3 Year 2005 about National Sport System. This study described about causes of regulation publishment, causes of conflict, type of conflict, the conflict’s impacts, managements and also constraints in solving the conflict. This study is qualitative research whose descriptive design.Result of this study is this conflict can be categorized as inter organizational conflict whose horizontal character. Sources of conflict are structure of organization, regulation, and also budgeting. According to Dahrendorf’s theory, conflict between two organizations had structural sources such as the question of power legitimacy. However, every conflict has a change.This research gave several recommendations in managing conflict. First of all, part of society, including the organization that involved in conflict, proposed a revise toward UU. No. 3 Year 2005 through Judicial Review Process in Constitutional Court (MK). Second, standing on UU No. 3 Year 2005 but doing synchronization and coordination way in derivative regulation. Third, publishing a new regulation that rules about sending of athletes to international events including making same qualification and same standard both sending and evaluation. This research also recommend to make target of change and using behavioral strategy to convert the conflict.Key Words: Conflict, Change, Regulation.